2021
DOI: 10.3892/ol.2021.12729
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation variations in familial female and male breast cancer

Abstract: In total, ~25% of familial breast cancer (BC) is attributed to germline mutations of the BRCA1 and BRCA2 genes, while the rest of the cases are included in the BRCAX group. BC is also known to affect men, with a worldwide incidence of 1%. Epigenetic alterations, including DNA methylation, have been rarely studied in male breast cancer (MBC) on a genome-wide level. The aim of the present study was to examine the global DNA methylation profiles of patients with BC to identify differences between familial female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Methylation of the BRCA1 promoter region is known to be one of the causes of breast cancer development in women [ 29 ] and has been reported as an oncogenic mechanism in familial breast cancer [ 30 ], but it was not detected in this study. It is possible that methylation of the BRCA1 promoter region does not contribute to carcinogenesis in Japanese patients with MBC; however, due to the small number of samples analyzed in this study, we cannot draw such a conclusion with certainty.…”
Section: Discussionmentioning
confidence: 57%
“…Methylation of the BRCA1 promoter region is known to be one of the causes of breast cancer development in women [ 29 ] and has been reported as an oncogenic mechanism in familial breast cancer [ 30 ], but it was not detected in this study. It is possible that methylation of the BRCA1 promoter region does not contribute to carcinogenesis in Japanese patients with MBC; however, due to the small number of samples analyzed in this study, we cannot draw such a conclusion with certainty.…”
Section: Discussionmentioning
confidence: 57%
“…Hong et al from South Korea theorized that the long gap between symptom onset and diagnosis was the main reason for the difference in the rate of occurrence of distant metastasis between MBC and FBC ( 17 ). Campos et al reported that BRCA1 and BRCA2 gene mutations were closely related to the occurrence of MBC ( 18 ), while Abeni et al demonstrated significant differences in DNA methylation between MBC and FBC in GTPase Rho GAP/GEF , GTPase RAB , BRCAX , BRCA1 + BRCAX , and other genes ( 19 ). Therefore, it is speculated that genetic differences may also contribute to the differing rates of distant metastasis in MBC versus FBC.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the molecular differences between the FBC and MBC methylomes, Abeni et al (2021) reported different DNA methylation levels of GTPase-related genes (RHO-GAP, RHO-GEF, and RAB GTPase) and keratin-related genes as an essential component of the cytoskeleton rearrangement biological process [119]. Known as key regulators of the cytoskeleton architecture, RHO GTPases are involved in membrane trafficking, gene transcription, cell migration, invasion, adhesion, survival and growth, and cancer initiation, metastasis and therapeutic responses [120].…”
Section: Biological Sex-and Gender-related Disparity In Breast Cancermentioning
confidence: 99%